2019
DOI: 10.1111/liv.14179
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of common therapies for Wilson disease: A systematic review and meta‐analysis of controlled studies

Abstract: Background & aims Wilson disease (WD) is a rare disorder of copper metabolism. The objective of this systematic review was to determine the comparative effectiveness and safety of common treatments of WD. Methods We included WD patients of any age or stage and the study drugs D‐penicillamine, zinc salts, trientine and tetrathiomolybdate. The control could be placebo, no treatment or any other treatment. We included prospective, retrospective, randomized and non‐randomized studies. We searched Medline and Embas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 85 publications
0
29
0
Order By: Relevance
“…While several studies have been done regarding the efficacy of chelating agents 13 and zinc, as well as comparing the various agents available for treatment of WD, 14,15,34,37 there is little to no commentary on dose adjustments or the most effective way to transition between different agents if necessary. As demonstrated by our patient above, patients may be transitioned between therapies for various reasons, whether it be inability to tolerate therapy due to adverse effects, ineffective treatment, comorbidities, or financial concerns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While several studies have been done regarding the efficacy of chelating agents 13 and zinc, as well as comparing the various agents available for treatment of WD, 14,15,34,37 there is little to no commentary on dose adjustments or the most effective way to transition between different agents if necessary. As demonstrated by our patient above, patients may be transitioned between therapies for various reasons, whether it be inability to tolerate therapy due to adverse effects, ineffective treatment, comorbidities, or financial concerns.…”
Section: Discussionmentioning
confidence: 99%
“…9,31 In our patient, despite compliance with zinc therapy, he had rising liver function tests, suggesting ineffective maintenance therapy with zinc. It has also been suggested that zinc may be as effective as chelators as initial therapy, 15,[32][33][34] especially in patients who are unable to tolerate chelating agents, who have significant neuropsychiatric disease, or in patients who are presymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, copper can bind to drugs in the bloodstream, mediate their passage through the damaged blood-brain barrier, and ultimately aggravate braintissue damage (Stuerenburg, 2000). Another hypothesis states that since the deposition of copper in nerve tissue may not be reversed in some patients with WD (even with the use of copperloading drugs, such as PCA) the neurological symptoms of these patients are irreversible, and PCA may even accelerate them (Appenzeller-Herzog et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The Wilson dataset [50] -from the field of medicine -is from a review on the effectiveness and safety of treatments of Wilson Disease, a rare genetic disorder of copper metabolism [33]. From the same field, the ACE dataset contains publications on the efficacy of Angiotensin-converting enzyme (ACE) inhibitors, a treatment drug for heart disease [32].…”
Section: Datasetsmentioning
confidence: 99%
“…Models were assessed by conducting a simulation on six systematic review datasets. To assess generalizability of the models across research contexts, datasets containing previous systeamtic reviews were collected from the fields of medical science [32,33,34], computer science [11], and social science [35,36]. The models, datasets and simulations are implemented in a pipeline of active learning for screening prioritization, called…”
Section: Introductionmentioning
confidence: 99%